European Quality Assurance from a policy perspective: where did we come from, where are we heading? - Tia Loukkola (Forum Neue Medien in der Lehre Austria, 2013)
The article presents some key developments in quality assurance (QA) on a European level over the last ten years. Particular attention is paid to discussing the impact of European QA policies (e.g. the European Standards & Guidelines) at the European and national level. This is done through a literature survey of recent policy studies, such as the Bologna Process progress reports. Taking stock, the article not only explores important issues related to QA (e.g. diversity or stakeholder participation) but also presents some likely future developments. 22.03.2013 | Tia Loukkola (Brussels)